Indirect indices of oxidative damage to phenolic compounds for the implementation of olive paste malaxation optimization charts. (August 2017) - Trapani, S.; Breschi, C.; Cecchi, L.; Guerrini, L.; Mulinacci, N.; Parenti, A.; Canuti, V.; Picchi, M.; Caruso, G.; Gucci, R.; Zanoni, B.
Abstract: An original kinetic study of the transformation phenomena of phenolic compounds in olive paste was carried out at different malaxation time-temperature conditions under exposure to air, using Abencor lab equipment to process olives (Frantoio cv) of a known degree of ripeness. Empirical kinetic models and the relevant apparent kinetic constants were determined for the following significant indices: total phenolic compound content in waste water samples using the Folin-Ciocalteu method; verbascoside and β-OH-verbascoside contents in olive paste samples using HPLC; and 3, 4-DHPEA-EDA contents in olive oil samples using HPLC. Two opposite phenolic compound transformation phenomena were proposed to explain the kinetic models: (i) enzymatic oxidative damage of phenolic compounds; (ii) physical and enzymatic release of phenolic compounds from cellular tissues. It was possible to propose a reference optimization chart to predict "selective" time-temperature conditions to maximize the apparent EVOO extraction yield while minimizing the degradation phenomena of phenolic compounds during malaxation. Highlights: An original experimental approach was used to study olive paste malaxation. A time-temperature kinetic study was applied to predict malaxation phenomena. Indices were selected to monitor oxidative damage to phenolic compounds. A reference synoptic chart was proposed to optimize malaxation.